2009
DOI: 10.1266/ggs.84.361
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of mutations induced by gamma irradiation in rice

Abstract: In order to analyze mutations induced by gamma irradiation in higher plants, we irradiated rice with gamma rays and screened for mutations expressing phenotypes of glutinous endosperm (wx), chlorophyll b deficiency, endosperm protein deficiency, gibberellin-related dwarfism, and shortened plastochron-in order to clarify types of mutations. Nucleotide sequence analysis showed that the most frequent mutation induced by gamma rays was deletion, particularly small deletion. Of the 24 mutations, 15 were small delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 51 publications
1
99
1
Order By: Relevance
“…1A and 3; Supplementary Fig. S1) in comparison to deletions that are induced by γ-rays (0%, Morita et al, 2009) and heavy ions with lower LETs (0% Fig. 3.…”
Section: Complex Rearrangement Induced By Fe-ion Irradiationmentioning
confidence: 98%
“…1A and 3; Supplementary Fig. S1) in comparison to deletions that are induced by γ-rays (0%, Morita et al, 2009) and heavy ions with lower LETs (0% Fig. 3.…”
Section: Complex Rearrangement Induced By Fe-ion Irradiationmentioning
confidence: 98%
“…On the other hand, the absence of 26 kDa globulin induced the collapse of PB-II structures in K × 433. Lgc1 and glb1 have deletions of a glutelin gene and the 26 kDa globulin gene, respectively (Kusaba et al 2003, Morita et al 2007). Glutelin and globulin are components of PB-II (Yamagata et al 1982), but the influence of their reduction on PB structure was different.…”
Section: Ultrastructure Of Protein Bodies During Seed Developmentmentioning
confidence: 99%
“…K × 433 is derived from a backcross of Koshihikari and the mutant line 89WPKG30-433 (Ashida et al 2006, Iida et al 1998 and shows the lack of a 26 kDa globulin, which is controlled by a single recessive gene, glb1. Morita et al (2007) reported that the glb1 mutant has a 63 kb deletion in a region including the 26 kDa globulin gene.…”
Section: Introductionmentioning
confidence: 99%
“…Gamma irradiation results in small deletions (1-10 bp) while neutrons cause 300 bp to 12 kbp deletions and chemical mutagens result in point mutations mainly G/C-to-A/T transitions (Morita et al, 2009). On the other hand, ion beams have high linear energy transfer (LET) ranging from 22.5 keV μm -1 to 4000 keV μm -1 compared to 0.2 to 2 keV μm 1 LET of γ-rays and X-rays (Ryuto et al, 2008).…”
Section: Developing 'Mutant' Resourcesmentioning
confidence: 99%